The BMP2 Signaling Axis Promotes Invasive Differentiation of Human Trophoblasts - You, Jiali; Wang, Wei; Chang, Hsun-Ming; Yi, Yuyin; Zhao, Hongjin; Zhu, Hua; Sun, Yu; Tang, Minyue; Wang, Chunyan; Sang, Yimiao; Feng, Guofang; Cheng, Shaobing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Embryo implantation and trophoblast invasion are principal limiting factors of pregnancy establishment. Aberrant embryo development or improper trophoblast differentiation and invasion may lead to various unfavorable pregnancy-related outcomes, including early pregnancy loss (EPL). Our clinical data show that the serum BMP2 levels were significantly increased during the first trimester of pregnancy and that the serum and BMP2 expression levels were lower in women with EPL than in women with normal early pregnancies. Moreover, we observed that BMP2 was expressed in oocytes and trophoblast cells of cleaved embryos and blastocysts prior to implantation in both humans and mice. Exogenous BMP2 promoted embryonic development by enhancing blastocyst formation and hatching in mice. LncRNA NR026833.1 was upregulated by BMP2 and promoted SNAIL expression by competitively binding to miR-502-5p. SNAIL induced MMP2 expression and promoted cell invasion in primary extravillous trophoblast cells. BMP2 promotes the invasive differentiation of mouse trophoblast stem cells by downregulating the expression of TS cell marker and upregulating the expression of trophoblast giant cell marker and labyrinthine/spongiotrophoblast marker. Our findings provide significant insights into the the regulatory roles of BMP2 in the development of the placenta, which may give us a framework to explore new therapeutic strategies to pregnancy-related complications.